2003
DOI: 10.1890/1051-0761(2003)013[0003:ateorc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Releasing Cod Larvae for Stock Improvement With Monitoring Data

Abstract: Beginning in the 1880s, management of marine fisheries by hatching and releasing yolk‐sac‐stage larvae was advocated in both the United States and Norway. Major cod hatchery programs were popular in both countries until the mid‐20th century, despite lack of evidence that cod abundance increases with release of hatchery‐reared fish larvae; the potential value for such management procedures was repeatedly advocated throughout the 20th century. In Norway, a beach‐seine monitoring program was begun in the early 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…For earlier studies that have used these data for ecological modelling, see Fromentin et al (1997Fromentin et al ( , 1998Fromentin et al ( , 2000Fromentin et al ( , 2001, Stenseth et al (1999), Bjørnstad et al (1999a,b) and Chan et al (2003a,b). Building upon the ecological model of Chan et al (2003b), we here extend the application of these monitoring data to testing the population genetic hypothesis suggested by Knutsen et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…For earlier studies that have used these data for ecological modelling, see Fromentin et al (1997Fromentin et al ( , 1998Fromentin et al ( , 2000Fromentin et al ( , 2001, Stenseth et al (1999), Bjørnstad et al (1999a,b) and Chan et al (2003a,b). Building upon the ecological model of Chan et al (2003b), we here extend the application of these monitoring data to testing the population genetic hypothesis suggested by Knutsen et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…While some projects have made an effort to disperse released fish (Støttrup et al, 2002), random distribution would best be replaced by targeted releases at a suitable density. Targeted stocking may even prompt a return to restocking the oceans (e.g., Chan et al, 2003), by releasing eggs into key oceanographic areas such as remotely sensed fronts or eddies.…”
Section: Targeted Stocking Approachmentioning
confidence: 99%
“…Parallel with this, a similar programme was launched in the northeastern USA (Earll, 1880;Solemdal et al, 1984). Recent statistical analyses have shown that these programmes did not result in any long-term increase in mature cod biomass in any of the relevant fjords/local areas (Chan et al, 2003). Coincidentally, from May to October 1983, the so-called breakthrough in cod rearing happened: 75 000 cultivated juveniles were collected in a 60 000-m 3 dammed pond at the IMR Austevoll Biological Station (Øiestad et al, 1985).…”
mentioning
confidence: 99%